Fatigue behavior of high strength steels under various levels of corrosion - Malíková, Lucie; Benešová, Anna; Al Khazali, Mohammad Sami; Seitl, Stanislav (Elsevier, 2024)
Propagation of a short fatigue crack directly from a corrosion pit is investigated within this work. A corroded rectangular specimen subjected to remote tensile cyclic loading is modelled via finite element method. Propagation of the angled crack is then controlled by both loading modes (I + II). A parametric study is performed to estimate the directions of further crack propagation for various geometrical configurations. Corrosion pit size is varied to simulate various levels of corrosion, and the analysis is carried out for a range of crack lengths and different initial crack inclination angles. Assumptions of linear elastic fracture mechanics are accepted, and classical maximum tangential stress criterion is applied to calculate the angles of crack deflection. Results obtained are discussed and are prepared to mutual comparison with observations of decrease of fracture mechanical/fatigue properties on real specimens subjected to relevant experiments.

Propagation of a short fatigue crack directly from a corrosion pit is investigated within this work. A corroded rectangular specimen subjected to remote tensile cyclic loading is modelled via finite element method. Propagation of the angled crack is then controlled by both loading modes (I + II). A parametric study is performed to estimate the directions of further crack propagation for various geometrical configurations. Corrosion pit size is varied to simulate various levels of corrosion, and the analysis is carried out for a range of crack lengths and different initial crack inclination angles. Assumptions of linear elastic fracture mechanics are accepted, and classical maximum tangential stress criterion is applied to calculate the angles of crack deflection. Results obtained are discussed and are prepared to mutual comparison with observations of decrease of fracture mechanical/fatigue properties on real specimens subjected to relevant experiments.
Fatigue behavior of high strength steels under various levels of corrosion
Keywords: High-strength steels; finite element analysis; corrosion pit; crack propagation; MTS fracture criterion; High-strength steels; finite element analysis; corrosion pit; crack propagation; MTS fracture criterion